2016
DOI: 10.1039/c6sc00355a
|View full text |Cite
|
Sign up to set email alerts
|

A quadrupolar two-photon fluorescent probe for in vivo imaging of amyloid-β plaques

Abstract: A quadrupolar two-photon fluorescent probe for in vivo imaging of amyloid-β plaques is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…The first is that the lack of the highly organized smooth muscles cells in veins and venules result in less substrates for Aβ deposition and, secondly, monocytes that exclusively adhere to veins might clear Aβ as it deposits along the venular walls [4,27,39]. In addition to the preclinical models discussed above, there are reports that do not distinguish between arteries and veins [60][61][62][63][64], or exclusively report of CAA in arteries [65,66]. Therefore, the present findings in this section address the need for characterization of all cerebral vessels to accurately gain a comprehensive understanding of both arterial and venous CAA.…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…The first is that the lack of the highly organized smooth muscles cells in veins and venules result in less substrates for Aβ deposition and, secondly, monocytes that exclusively adhere to veins might clear Aβ as it deposits along the venular walls [4,27,39]. In addition to the preclinical models discussed above, there are reports that do not distinguish between arteries and veins [60][61][62][63][64], or exclusively report of CAA in arteries [65,66]. Therefore, the present findings in this section address the need for characterization of all cerebral vessels to accurately gain a comprehensive understanding of both arterial and venous CAA.…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…Fluorescence-based imaging has emerged as an increasingly important technique for monitoring diseases, 9,10 and possesses several advantages, including lower cost, no exposure to radioactivity, availability and ease of operation. 11,12 Even though there are a variety of fluorescent probes for detecting Aβ aggregates, [13][14][15][16][17][18][19] fluorescent probes that can specifically distinguish Aβ oligomers from Aβ fibrils are rare. Ran et al reported a fluorescent probe, CRANAD-58, which exhibited a significant increase in fluorescence intensity upon mixing with Aβ monomers and oligomers.…”
Section: Spiropyran-based Fluorescent Probe For Specific Detection Ofmentioning
confidence: 99%
“…A potential route to identify efficient two-photon sensors for β-amyloid imaging is to explore the two-photon properties of the dyes that have already shown some success in this aspect. Up to now, plenty of fluorescent probes with multiple chemical structures have been synthesized and experimentally applied to detect the β-amyloid plaques in vivo, such as PAD-1, DCIP-1, and BAP-1 with donor-acceptor architecture [16][17][18], and QAD1, DADNIR-2, and CRANAD-3 with donor-acceptor-donor architecture [19][20][21]. Due to some correlations between the donor-π-acceptor structural compounds and their optical properties that have already been established [22,23], we choose molecules with the N,N-dimethylamino group as the donor and dicyano group as the acceptor to study their possibility to be two-photon fluorescent probes for detecting β-amyloid.…”
Section: Introductionmentioning
confidence: 99%